Synthesis Report - Urbanization and Farm Size - Masters, William A. (CGIAR Independent Science and Partnership Council, 2013)
This report summarizes findings from an ISPC Foresight Study asking what urbanization and farm size and other major trends imply for CGIAR agricultural research priorities. The study is based on 5 background papers reviewed by 15 discussants and debated during a 2-day workshop, then revised and synthesized in this document.